1971
DOI: 10.1111/j.1476-5381.1971.tb07125.x
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of chlorpromazine during absorption in the rat in vivo and in vitro

Abstract: Summary Concentrations of total radioactivity in plasma of rats given intravenous and oral 35S‐chlorpromazine, were similar. Concentrations of unchanged drug, however, were lower after oral doses. Chlorpromazine circulated in solution through isolated loops of rat intestine was rapidly absorbed by the tissue. Measurements of glucose transport and histological examination indicated that the tissue was intact. In these in vitro experiments some of the chlorpromazine was converted to products, which together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…Following the observation that chlorpromazine was metabolised by an intestinal tissue preparation in vitro (Curry et al, 1971), the importance of gut wall metabolism of orally administered phenothiazines * Present address: Welsh School of Pharmacy, U.W.I.S.T., Cathays Park, Cardiff CF1 3NU 0306-5251/83/0300-0287 $02.00 has been widely accepted (Curry, 1976;Lader, 1976;Cooper, 1978;Davis et al, 1978). The evaluation of this hypothesis in man is difficult due to several technical and ethical problems.…”
Section: Introductionmentioning
confidence: 99%
“…Following the observation that chlorpromazine was metabolised by an intestinal tissue preparation in vitro (Curry et al, 1971), the importance of gut wall metabolism of orally administered phenothiazines * Present address: Welsh School of Pharmacy, U.W.I.S.T., Cathays Park, Cardiff CF1 3NU 0306-5251/83/0300-0287 $02.00 has been widely accepted (Curry, 1976;Lader, 1976;Cooper, 1978;Davis et al, 1978). The evaluation of this hypothesis in man is difficult due to several technical and ethical problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, with drugs like CPZ, which are highly and tightly bound to the gut walliS and metabolized in the gut, 4 slow gastric emptying can result in a decrease in both plasma peak levels and the area under the concentration-time curve. A study of the effect of lithium on gastric emptying in mans failed to demonstrate a consistent effect.…”
mentioning
confidence: 98%
“…Hence, the low water solubility of ET by itself could explain the low oral bioavailability. In addition, presystemic metabolism by the gastrointestinal tract has been proposed to influence the bioavailability of another phenothiazine derivative, chlorpromazine [14]. Although it has been shown that intestinal metabolism of chlorpromazine can occur in vitro, the significance of this pathway towards reducing oral bioavailability has been the center of some attention.…”
Section: Resultsmentioning
confidence: 99%